A hybrid approach for real-time sentiment analysis & visualization of tweets in Singlish - Lim, Michelle Shi Hui (2018)
In the Social Age today, the number of people turning to social media sites to voice their opinions is increasing at a staggering rate. Since there lies such a great amount of sentiment-filled text on Twitter, this arises as a great opportunity to be used as a platform for understanding the public’s attitudes on certain topics. Such information can be useful in generating insights in business, social and political contexts, to aid informed decisions.